2013
DOI: 10.1158/0008-5472.can-13-1142
|View full text |Cite
|
Sign up to set email alerts
|

Myoferlin Is a Key Regulator of EGFR Activity in Breast Cancer

Abstract: Myoferlin is a member of the ferlin family of proteins that participate in plasma membrane fusion, repair, and endocytosis. While some reports have implicated myoferlin in cancer, the extent of its expression in and contributions to cancer are not well established. In this study, we show that myoferlin is overexpressed in human breast cancers and that it has a critical role in controlling degradation of the epidermal growth factor (EGF) receptor (EGFR) after its activation and internalization in breast cancer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
100
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(109 citation statements)
references
References 36 publications
8
100
1
Order By: Relevance
“…Our laboratory recently described myoferlin as a key regulator of EGFR activity in breast cancer. 16 In endothelial cells, it was found to regulate VEGFR2 biological activity through preventing its polyubiquitination and its subsequent degradation by the proteasome. 4 In the same cell type the expression of angiopoietin-1 receptor (TIE-2) seemed to be myoferlin-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory recently described myoferlin as a key regulator of EGFR activity in breast cancer. 16 In endothelial cells, it was found to regulate VEGFR2 biological activity through preventing its polyubiquitination and its subsequent degradation by the proteasome. 4 In the same cell type the expression of angiopoietin-1 receptor (TIE-2) seemed to be myoferlin-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…5E). Likewise, myoferlin (MYOF), a gene linked to breast cancer progression (36) and metastasis of pancreatic carcinoma (37), was downregulated in Colo-205 cells (Fig. 5B and Supplementary Fig.…”
Section: B-rafmentioning
confidence: 97%
“…It had been first identified in muscle cells, where it contributes to cell/cell fusion and muscle regeneration [15, 16]. Further studies performed in endothelial cells demonstrated that myoferlin is important for membrane repair and endocytosis [17] as well as receptor-mediated angiogenesis [1821]. In cancer, overexpression of the protein has been reported in breast, lung, and pancreatic tumors [2225], where it is associated with increased tumorigenic potential and angiogenesis [21, 2628].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies performed in endothelial cells demonstrated that myoferlin is important for membrane repair and endocytosis [17] as well as receptor-mediated angiogenesis [1821]. In cancer, overexpression of the protein has been reported in breast, lung, and pancreatic tumors [2225], where it is associated with increased tumorigenic potential and angiogenesis [21, 2628]. Mechanistically, myoferlin has been shown to control both endocytosis (EGFR, VEGFR2, IGFR and Tie-2) and exocytosis (VEGF) of several key molecules [1821, 28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation